Prevalence of transfusion transmitted infections amongst multiple blood transfused patients of β-thalassemia major in a tertiary care hospital - Mittal, Kundan; Abrol, Pankaj; Yadav, Jaivinder (International Journal of Research in Medical Sciences, 2016)
Background: The β-thalassemias are the most common autosomal recessive inherited hemoglobin disorder in the Indian subcontinent, with an uneven distribution among different endogenous populations. Present study was planned to estimate the prevalence of transfusion transmitted viral diseases in multiple transfused patients of β-thalassemia and factors affecting it. Methods: It was a Prospective observational study carried out at Thalassemia day care center of tertiary health care institute. Results: 211 patients were enrolled in the study. 151 were males and 60 females. Maximum numbers of children were in age group of 6- 10 years. 75 (35.5%) patients with HCV (Hepatitis C Virus) and 5 (2.36%) patients with Hepatitis B virus (HBV) infection were found at the end of study. No new HIV (Human Immunodeficiency Virus) infection was detected. There was significant association between prevalence of transfusion transmitted infections (TTI) with number of transfusions but no significant association detected with age, sex and blood group of the patients Conclusions: Thalassemia is a chronic transfusion dependent disease complicated by the effects of iron overload on various organs leading to increased morbidity and mortality. The risk of transmission of TTI in thalassemia increases with time as number of transfusions increase. Use of advanced technology in blood screening, voluntary donations, donor selection, asepsis during blood transfusion should be used to curtail the transmission.